RETURN OF STATE FINANCIAL LOSSES IN THE FORM OF COMPENSATION PAYMENTS BY CONVICTED CORRUPTION OFFENDERS - Subrata, Tedy; Markuat, Markuat (Hukum Responsif, 2025)
This research aims to understand the legal policies regarding the restitution of state financial losses in the form of monetary compensation by convicted corruption offenders and to identify the efforts made by police investigators in addressing the challenges of recovering state financial losses in the form of monetary compensation by convicted corruption offenders. The method used in this research is qualitative, with a primary approach of normative juridical and supporting approaches of empirical juridical. The data sources used in this research were obtained from secondary data as the primary data and from primary data as the supporting data. Furthermore, the data were subsequently processed using qualitative methods. The research findings reveal that the classification of corruption crime penalties and fines has been regulated by Law No. 31 of 1999 concerning the Eradication of Corruption Crimes, which has since been amended by Law No. 20 of 2001. The amount of restitution and compensation is at most equal to the value of the assets obtained from the act of corruption. If the substitute money is not paid, the offender will be punished with additional fines that do not exceed the maximum limit of the principal penalty. Therefore, the compensation for the loss of the national currency is not optimal. The amount of compensation for state losses needs to be linked with the implementation of restitution and compensation for the assets/wealth of the perpetrators. The Asset Recovery Law needs to be established as a legal framework for the recovery of assets from corruption proceeds.